Preparation and Adsorption Properties of Pd Nanoparticles Supported on TiO2 Nanotubes - Honciuc, Andrei; Laurin, Mathias; Albu, Sergiu; Amende, Maximilian; Sobota, Marek; Lynch, Robert; Schmuki, Patrik; Libuda, Jörg (Journal of Physical Chemistry C, 2010)
Here we present preparation methods for a series of novel model heterogeneous catalysts consisting of Pd nanoparticles dispersed on self-organized TiO2 nanotube arrays (TiNTs). For a comprehensive comparative study of TiNTs' surface adsorption properties, different chemical and physical methods were employed for the deposition of the Pd nanoparticles: (i) e-beam deposition in high vacuum (HV) and (ii) in ultrahigh vacuum (UHV), (iii) impregnation, and (iv) metal precipitation. Following preparation, the Pd/TiNTs were exposed to several O-2 (oxidative) and CO (reductive) cleaning cycles at 500 K in UHV. After each cleaning cycle, the CO adsorption properties were systematically probed with time-resolved infrared reflection-adsorption spectroscopy to monitor the surface state of the catalyst. It is shown that clean and well-defined Pd/TiNT catalysts can be obtained, which are well suited for future adsorption and reactivity studies.